Real-time pressure monitoring system for microfluidic devices using deformable colloidal crystal membrane - Choi, Jang Han; Shim, Tae Soup (Lab on a Chip, 2019)
Understanding the hydrodynamic behavior in microfluidic devices is crucial for utilization of these systems in lab-on-a-chip applications. However, hydrodynamic capacitance in microfluidic devices causes a delay and mismatch between the applied pressure and actual pressure in the microchannel. Therefore, real-time monitoring of the site-specific internal pressure in microchannels is important for designing the operating conditions of the system. We introduce a deformable colloidal crystal membrane composed of polystyrene (PS) colloidal crystals and poly(dimethylsiloxane) (PDMS) and its integration into a PDMS microfluidic device. As pressure is applied to the device, the optical intensity reflected back from the colloidal crystal membrane changes due to membrane deformation. The optical signal originating from structural deformation of the colloidal crystal membrane allows the realization of a real-time pressure monitoring system, as no external apparatus or powering devices are required for signal processing. The internal pressure in microfluidic devices was also monitored to investigate the effect of the hydrodynamic capacitance during pressure application.
Keywords: Hydrodynamic behavior; Lab-on-a-chip applications; Micro-fluidic devices; PDMS microfluidic device; Polydimethylsiloxane PDMS; Pressure applications; Real time monitoring; Structural deformation